A realidade virtual como recurso educativo: o uso da tecnologia por professores de Biologia - OLIVEIRA, Carlos Bruno Cabral de (2020)
Virtual Reality (VR) consists in immersing into a digital environment, commonly with the aid of a head-mounted display (HMD) which projects images directly to the user’s eyes. To Biology education, VR potentialities englobe an immersion into biomes, the virtual representation of animals, the exploration of macro and microstructures etc. Specific cares also need to be taken into account when planning lessons with RV, which demands an attentive look by the teacher. We aimed to analyze the use of Virtual Reality by Biology teachers. For such, we carried a case study as a qualitative research, and we submitted the obtained data to content analyzes, which had three stages: pre-analysis, exploration of the material, and interpreting and inferring the obtained data. Thus, as an intervention propose, we offered a workshop about VR for Biology teachers from the Centro Educa Maus Dayse Galvão de Sousa school, located in São Luís, MA. The workshop had two segments: one theory-based, in which we traced a brief history of technologies in Education, followed by an explanation about the potentialities of VR to Biology teaching; and one practice-based, when we had VR activities using smartphones and low-cost HMD. By the end of the workshop, we applied a questionnaire with open questions to collect data from the participants. Regarding the analyses, we organized the results into two categories: Perceptions about VR; and VR and Biology education. We can affirm that VR potentialities for Biology teaching are diverse and a careful look to both technical and pedagogical aspects, such as the language of the materials and internet availability, are necessary in order to develop such potentialities during the lessons. For the research product, as academic product we elaborated an ebook about VR in Biology Education for teachers of the referred subject.